De la Turquie à la région lyonnaise : lettre d’un immigré arménien sur les mûriers et le ver à soie (1938) - Philippe Videlier (Diasporas: Circulations, Migrations, Histoire)
When the Decines artificial silk factory opened after First World War in the Lyon suburb, a big wave of immigrants came to France after a chaotic journey to take up unskilled industrial jobs. Among them were an important number of Armenians survivors from the genocide committed under the former Ottoman Empire. Arriving in a foreign country they brought with them a rural culture with some surprises: for instance a worker knowledgeable about natural silk and mulberry bushes and an admirer of Louis Pasteur.